Cyberbullying pada Remaja di TikTok Official Account @Cimoycantik12 - Nur Hidayati, Ayuk; Noor Rakhmad, wiwid; Hasfi, Nurul (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
TikTok is media that currently popular among teenagers. The convenience and freedom in accessing TikTok provide teenagers with the freedom to be creative and expressive. In addition to being creative and expressive, the convenience and freedom offered by TikTok also make it a place for cyberbullying. Cyberbullying is an issue and a social phenomenon resulting from misuse of TikTok. One of the cases of cyberbullying on TikTok was experienced by the account @Cimoycantik12, who received insulting comments, taunts, and insults from teenagers through her comments section. In that case, this research aimed to describe what forms of cyberbullying are given by the perpetrators on the official TikTok account @Cimoycantik12 and analyze the various reasons for the perpetrators in cyberbullying on the official TikTok account @Cimoycantik12.The research utilized Alfred Schutz's phenomenological approach and the General affective aggression model (GAAM) by involving 5 teenagers (aged 18-24 years) who had committed cyberbullying on TikTok account @Cimoycantik12. It is qualitative research with a phenomenological approach. The results of this study indicate that the form of cyberbullying that occurs is carried out by teenagers as perpetrators is an action that they consciously take because of the personal experience of the perpetrator who has also been a victim of cyberbullying and the factor of the victim in this study, @Cimoycantik12, which provokes the perpetrators to commit acts of cyberbullying against him. The form of cyberbullying found in the official TikTok @Cimoycantik12 is a form of flaming and harassment carried out through the TikTok @Cimoycantik12 comment column. The reason for teenagers as perpetrators of cyberbullying on the official TikTok @Cimoycantik12 account is because the perpetrators consider that the TikTok @Cimoycantik12 content is less educational, not in accordance with the ethics of social media in adolescence which should trigger the perpetrators to carry out cyberbullies.